Child psychoanalysis: the legitimacy of a field - Rosenberg, Ana Maria Sigal (Clinical Styles. The Journal on the vicissitudes of childhood, 1999)
Borrowing from J. Laplanche body of thought the concept of enigmatic significant and the genemi seduction theory, this article brings forth matters related to the inclusion of parents in children psychoanalysis. As we know, it is not only the symbolic or imaginary parents who circulates within the psychoanalytic setting, real parents also do so, compelling the analyst to work at the very boundaries between reality and phantasy. From this perspective, we believe the psychoanalysis process produces rearrangements and reditions, which may very well benefitfrom actual parents presence.